2020
DOI: 10.5897/err2019.3850
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of psychometric properties of mathematics items constructed by Waec and Neco in Nigeria using item response theory approach

Abstract: West Africa Examination Council (WAEC) and National Examination Council (NECO) are the two major examination bodies saddled with the responsibility of awarding Senior Secondary School Certificate in Nigeria. This study examined the comparability of the psychometric properties of the items constructed by the two examination bodies using Item Response Theory (IRT) approach. Three parameters (difficulty, discriminating and distrator Indices) logistic model was adopted for the study. The study employed descriptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 3 publications
(4 reference statements)
1
4
0
Order By: Relevance
“…This implies that although NECO does not disclose the psychometric properties of the items she uses for the tests she conducts, it does not in any way suggest that the quality of the items used may be of low quality. These findings are consistent with the findings earlier made by [15] who revealed that the items used by NECO are of adequate quality for use in the tests she conducts since their psychometric properties; difficulty, discrimination, distracter indices as well as guessing factors were adequate. Also lending a voice to the adequacy of the NECO's items, [20] and [21] reported that the difficulty parameter of test items constructed by public examining bodies in Nigeria, NECO inclusive, were adequate.…”
Section: Discussion Of Findingssupporting
confidence: 91%
See 4 more Smart Citations
“…This implies that although NECO does not disclose the psychometric properties of the items she uses for the tests she conducts, it does not in any way suggest that the quality of the items used may be of low quality. These findings are consistent with the findings earlier made by [15] who revealed that the items used by NECO are of adequate quality for use in the tests she conducts since their psychometric properties; difficulty, discrimination, distracter indices as well as guessing factors were adequate. Also lending a voice to the adequacy of the NECO's items, [20] and [21] reported that the difficulty parameter of test items constructed by public examining bodies in Nigeria, NECO inclusive, were adequate.…”
Section: Discussion Of Findingssupporting
confidence: 91%
“…The findings of [22] in a study designed to assess the items prone to guessing in SSCE economics multiple-choice tests among students in Kwara State, Nigeria, lend a voice to this when it reported that the items used by NECO are of adequate quality for use in the tests she conducts. [15] also supports this finding when they reported that the items used by NECO are of adequate quality for use in the tests she conducts since their psychometric properties; difficulty, discrimination, distracter indices as well as guessing factors were adequate. Guessing has a way of negatively impacting on the credibility of test scores.…”
Section: Discussion Of Findingsmentioning
confidence: 53%
See 3 more Smart Citations